Ultrathin optically transparent metamaterial absorber for broadband microwave invisibility of solar panels. (20th October 2021) - Li, Shuying; Liu, Liangliang; Jiang, Yuying; Tang, Chunzi; Gu, Changqing; Li, Zhuo
Abstract: In this paper, we propose an ultrathin optically transparent metamaterial absorber (OTMMA) for broadband microwave invisibility of solar panels. The OTMMA is a multi-layered structure consists of a continuous indium tin oxide (ITO) film layer, a polymethyl methacrylate substrate layer, and an ITO film layer etched with periodic square split resonance rings. Under normal incidence, the OTMMA exhibits more than 90% absorptivity from 7.82 to 17.15 GHz with arbitrary polarization. At oblique incidence, the absorptivity of the OTMMA reaches over 75% for transverse electric polarization when the incident angle is not more than 50°, whereas it is over 80% for transverse magnetic polarization with an incident angle not greater than 75°. An OTMMA sample with a thickness of λ 0 /11 is fabricated and attached to the surface of a 300 × 300 mm 2 solar panel for measurement. Excellent agreement between the simulated and measured absorptivity verify our design, showing that the OTMMA can achieve 93%–99% absorption of electromagnetic waves in the whole X-band while ensuring the efficient light transmittance of the solar panels.